2001
DOI: 10.1108/02651330110398387
|View full text |Cite
|
Sign up to set email alerts
|

Strategic issues of e‐commerce as an alternative global distribution system

Abstract: Global e-commerce, created by the convergence of information and communication technologies, transcends business boundaries while changing the landscape of the twenty-first century global economy. Although still in an infancy stage its impact has already been colossal in just a few years. Various constituencies (such as individuals, institutions, governments, and nations) around the world are recognizing its benefits. Given its importance and unprecedented growth potential, there is a need for research address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 20 publications
0
70
0
4
Order By: Relevance
“…In addition to the theoretical basis described above, the framework has also been influenced by research models proposed in earlier studies [10,28,27]. Jayawardhena and Foley [28] proposed that changes in technological, cultural, commercial and legal factors, together with the competitive forces of financial services market, drive financial services development.…”
Section: Framework For the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the theoretical basis described above, the framework has also been influenced by research models proposed in earlier studies [10,28,27]. Jayawardhena and Foley [28] proposed that changes in technological, cultural, commercial and legal factors, together with the competitive forces of financial services market, drive financial services development.…”
Section: Framework For the Literature Reviewmentioning
confidence: 99%
“…Jayawardhena and Foley [28] proposed that changes in technological, cultural, commercial and legal factors, together with the competitive forces of financial services market, drive financial services development. Javalgi and Ramsey [27] suggested that information technology and telecommunication, social/cultural, commercial, and government/legal factors impact the diffusion of global eCommerce. Dahlberg and Mallat [10] combined these two models to describe factors which characterize mobile payment services markets and impact the diffusion of these services.…”
Section: Framework For the Literature Reviewmentioning
confidence: 99%
“…Increasing demand of international brands and services clearly depicts the rapid expansion of businesses to international markets (Javalgi & Ramsey, 2001). Because of this increasing expansion of businesses to international markets small and medium enterprises are facing a great pressure of competitors to internationalize their business for their survival and growth.…”
Section: Entrepreneurial Orientation and Internationalization Relatiomentioning
confidence: 99%
“…Pelaku bisnis dapat melakukan transaksi perdagangan dimana pun dan kapanpun selama ia terhubung ke internet. Ecommerce melibatkan transaksi antara penjual dan pembeli, beserta proses internal didalamnya (Javalgi dan Ramsey, 2001). Semua transaksi perdagangan tersebut dilakukan tanpa memerlukan tatap muka antara pihak penjual dan pihak pembeli.…”
Section: Pendahuluanunclassified